A young man with an atypical liver mass: Focal nodular hyperplasia - Uyar, Seyit; Sukru Alparslan, Ahmet; Aydin, Demet; Celik Erdogan, Betul; Kavas, Gamze; Bostan, Feyzi (Annals of Medical Research, 2021)
None
Keywords: Benign liver tumors; focal nodular hyperplasia; diagnosis